Inovasi dalam Terapi Pengobatan Tuberkulosis dan Penerapannya di Indonesia - Hidayat, Rizqi; Oktarlina, Rasmi Zakiah; Romulya, Ari Irawan (Medula, 2024)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis, which can affect various organs, especially the lungs. It is transmitted through the air, making it a global health problem. In Indonesia, the number of TB cases is quite significant, indicating serious challenges in handling this disease. In an effort to improve the effectiveness of health services, service innovations need to be developed with a focus on providing comfort for Tuberculosis (TB) patients during the treatment process. This study examines innovations in TB treatment therapy in Indonesia with a focus on understanding, identifying and addressing critical barriers to TB treatment. This research highlights the importance of innovations in TB treatment as a solution to overcome healthcare access barriers, improve efficiency, and reduce geographical barriers. Forms of innovation in TB treatment include diverse approaches to improve treatment effectiveness. Mobile Health (mHealth) provides health access solutions for individuals in remote areas through mobile technology. Digital Health, such as SMS and Voice over Text (VOT), supports patient monitoring and treatment success, requiring government technology infrastructure support. Telemedisin facilitates real-time communication between patients and health workers, minimizing the risk of treatment discontinuation. Innovative programs, such as TOSS-TB and BATAS PETIR, demonstrate success through political, economic, social support, and technology implementation. The use of technology for MDR tuberculosis involves a holistic approach, integrating technology, economic support, and social aspects. Continuous evaluation and adaptation of innovations are key to improving TB control outcomes globally.